(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract: As we all know, the role and importance of hearing in the art of music is extremely important. After all, through the ability of hearing, the child, first of all, feels the melody he is playing, understands the tone of the piece. In addition, it is easier for a student with well-developed auditory skills to learn the lessons during performance and during the lessons. This article is about hearing aids and how to develop them